Performance of SMK Dian Kirana 1 Sragen Teachers Reviewed from Commitment, Integrity, Supervision and Work Experience - Sugito; Istiatin; Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the influence simultaneously (simultaneously) and partially of the variables of commitment, integrity, supervision and work experience on the performance of teachers at SMK Dian Kirana 1 Sragen. This research method uses a quantitative research design. The population in this study were all teachers who worked at Vocational School Dian Kirana 1 Sragen, totaling 40 people. The sampling technique used in this research was a census sampling technique with a sample size of 40 respondents. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that commitment, integrity, supervision and work experience simultaneously and significantly influence the performance of teachers at Dian Kirana 1 Sragen Vocational School. Suggestions from this research, Dian Kirana 1 Vocational School Sragen continues to improve existing commitment, integrity, supervision and work experience, so that teacher performance will increase and be better than before.